Strategi Evaluasi Kinerja Guru Sebagai Upaya Peningkatan Kualitas Pendidikan di Sekolah Dasar - Bella Apriliza Putri; Hury Prananda; Suci Cahaya Mentari (Universitas Serambi Mekkah, 2025)
Clinical supervision is a strategic approach to improve the quality of education, especially at the elementary school level, by involving collaboration between supervisors and teachers. This study aims to analyze the effectiveness of clinical supervision in improving teachers' pedagogical competence and identifying challenges in its implementation. The method used is a literature study, where data is collected from related scientific articles in the last seven years. The data collection process involves an in-depth analysis of previous research results, which are relevant to the topic of clinical supervision. Overall, clinical supervision has proven to be a relevant and adaptive approach to addressing the challenges of modern education, especially in 21st century learning. This study recommends special training for supervisors and a flexible approach to improve the effectiveness of clinical supervision implementation. The results of the study are expected to be a practical reference for educators and policy makers in supporting the improvement of the quality of education in Indonesia